1989
DOI: 10.7326/0003-4819-111-4-297
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Deep-Vein Thrombosis Using Duplex Ultrasound

Abstract: Duplex ultrasound appears to be very accurate in the detection of acute proximal deep-vein thrombosis. This test has major advantages as well as certain limitations compared with other diagnostic methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(77 citation statements)
references
References 40 publications
1
74
0
Order By: Relevance
“…Although contrast venography has been considered as the gold standard for the diagnosis of DVT (4), it is invasive and requires contrast media. Presently, duplex and compression ultrasonography is the preferred technique to image flow in the proximal veins of the lower leg (5). It combines morphological (e.g., thrombus) and functional aspects (e.g., venous flow) with a functional stress test such as gentle pressure on the veins (i.e., compression).…”
Section: Introductionmentioning
confidence: 99%
“…Although contrast venography has been considered as the gold standard for the diagnosis of DVT (4), it is invasive and requires contrast media. Presently, duplex and compression ultrasonography is the preferred technique to image flow in the proximal veins of the lower leg (5). It combines morphological (e.g., thrombus) and functional aspects (e.g., venous flow) with a functional stress test such as gentle pressure on the veins (i.e., compression).…”
Section: Introductionmentioning
confidence: 99%
“…The overall sensitivity is 93% (range 87-100%) and the overall specificity is 94% (range 78-100%) [94][95][96][97][98], In a recent study it was shown that US and duplex are methods with comparable high accuracy. Because of its availability, accu racy, cost-effectiveness and simplicity US was rec ommended as the primary diagnostic test [99].…”
Section: (Colour) Duplex Scanningmentioning
confidence: 97%
“…Although the D-dimer assay has a high negative predictive value (96-100%), which allows exclusion of VTE [3][4][5], its specificity is only 36-44% [15,16]. On the other hand, lower extremity venous ultrasonography has high sensitivity (93-96%) as well as high specificity (98-99%) for the diagnosis of DVT [6][7][8]. However, ultrasonography in all preoperative patients as a screening tool is considered to represent overuse of this diagnostic resource [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The D-dimer assay is a safe and useful tool with a high sensitivity (97-100%) for excluding DVT and a high negative predictive value (96-100%) [3][4][5]. Lower extremity venous ultrasonography is the standard method for the diagnosis of DVT, with a high sensitivity (93-96%) and high specificity (98-99%) [6][7][8]. In July 2012, we started preoperative DVT screening at our institution using a combination of D-dimer measurements and lower extremity venous ultrasonography in patients undergoing gastric cancer surgery.…”
Section: Introductionmentioning
confidence: 99%